Leadership Education: Leaders of Achievement and Character in the Bible and the Secular World - Dolok Bend Franki Pane; Stimson Hutagalung; Exson Eduaman Pane; Janes Sinaga (Jurnal Multidisiplin Madani, 2023)
Throughout its history, quality management has been an important factor in the success of an organization, both in the business world and in the world of education, government, politics, health and religion. There are many leaders in this world, but there are not many leaders who are good and have character. To have a model for the character of a leader we can find in the Bible and antecedents dedicated to the larger community. The purpose of this study is for every leader and prospective leader to emulate biblical figures and their predecessors so that their leadership is ultimately successful. This study uses descriptive qualitative methods through literature analysis and observations related to leadership character and performance. To become a leader with achievement and character, the leader can imitate the leadership model of the Bible and secular world leaders who have proven their leadership and influence on the lives of the people they lead. Characters that can be emulated from them are piety, loyalty, honesty, humility, holding fast to God and having integrity